2022
DOI: 10.3390/genes13050851
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cuproptosis-Related Prognostic Gene Signature and Validation of Differential Expression in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most prevalent subtype of renal cell carcinoma, which is characterized by metabolic reprogramming. Cuproptosis, a novel form of cell death, is highly linked to mitochondrial metabolism and mediated by protein lipoylation. However, the clinical impacts of cuproptosis-related genes (CRGs) in ccRCC largely remain unclear. In the current study, we systematically evaluated the genetic alterations of cuproptosis-related genes in ccRCC. Our results revealed that CDKN2A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
201
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(215 citation statements)
references
References 49 publications
10
201
2
2
Order By: Relevance
“…In previous studies, it was found that the copper depletion caused by tetrathiomolybdate (TM) influences immune response, and intratumoral copper ions may be able to regulate PD-L1 expression and influence tumor immune escape ( 9 , 10 ). Consistently, the latest report of Bian et al also showed that cuproptosis was significantly correlated with immune cell infiltration and PD-1 expression in clear cell renal cell carcinoma (ccRCC) ( 11 ). In addition, copper, platinum, and iron as raw materials have been extensively studied in the development of drug delivery systems, showing promising prospects for a range of anticancer purposes ( 12 ).…”
Section: Introductionsupporting
confidence: 63%
“…In previous studies, it was found that the copper depletion caused by tetrathiomolybdate (TM) influences immune response, and intratumoral copper ions may be able to regulate PD-L1 expression and influence tumor immune escape ( 9 , 10 ). Consistently, the latest report of Bian et al also showed that cuproptosis was significantly correlated with immune cell infiltration and PD-1 expression in clear cell renal cell carcinoma (ccRCC) ( 11 ). In addition, copper, platinum, and iron as raw materials have been extensively studied in the development of drug delivery systems, showing promising prospects for a range of anticancer purposes ( 12 ).…”
Section: Introductionsupporting
confidence: 63%
“…Accumulating evidence have shown that the development of tumors is always related to programmed cell death (20-22). Bian Z et al constructed a cuproptosis-related prognostic gene signature in clear cell renal cell carcinoma, confirming the importance of cuproptosis in tumor development and progression (23). In-depth research in cuproptosis helps to facilitate new understandings of the pathogenesis of tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Cuproptosis a novel form of copper-induced cell death has been reported to be regulated by 16 mRNAs as described above. Besides, previous study has constructed prognostic signature using cuproptosis related mRNA based on TCGA-KIRC cohort (12). The AUC of 1-year, 3-year, and 5-year survival for ccRCC patients in their study was 0.652, 0.633, and 0.658, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have constructed the signatures with cuproptosis related mRNAs (12) or lncRNAs (13) to predict the prognosis of ccRCC patients basing on the TCGA-KIRC cohort only. However, the prognostic value of signature constructed with CRLM for ccRCC patients has not been reported before.…”
Section: Introductionmentioning
confidence: 99%